David Flower: Editor-in-chief, Monthly Notices of the RAS. Issue 3 (1st June 2021) - Flower, David
Abstract : The astronomer has served on the MNRAS editorial board for more than 35 years, and since 2012 has steered it as it picked up speed through the digital age. Interview by Paul Johnson Abstract: The astronomer has served on the MNRAS editorial board for more than 35 years, and since 2012 has steered it as it picked up speed through the digital age. Interview by Paul Johnson